Critical Knowledge Gaps in Iraqi Nurses' Understanding of Antihypertensive Drug Risks : Kesenjangan Pengetahuan Kritis dalam Pemahaman Perawat Irak tentang Risiko Obat Antihipertensi - Wasfi Dhahir Abid Ali; Samahir Sabri Hamid; Muhammed Sabah; Zahrraa Mahmood Hussain Al-Hijaj; Sundos Baker; Maher A. Atiyah (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Poor adherence to antihypertensive medications and persistently elevated blood pressure contribute significantly to cardiovascular events, increased hospitalizations, and premature mortality. Specific Background: Adverse effects of antihypertensive medications, such as cough, dizziness, and increased urination, often lead to non-adherence, exacerbating these health risks. Knowledge Gap: There is limited understanding of nurses' knowledge regarding the adverse effects of antihypertensive medications, particularly in developing regions. Aims: This cross-sectional study aimed to evaluate the knowledge of nurses in Basra, Iraq, about the adverse effects of antihypertensive medications and to identify areas needing improvement. Results: Seventy nurses (both male and female) from various hospitals in Basra participated in a questionnaire. Findings revealed that only 49.78% of nurses were confident in their knowledge about the adverse effects of these medications, 20% did not know the answers, and 25.9% were unsure. The overall mean score was significant (2.27), indicating insufficient knowledge. Novelty: This study provides the first detailed assessment of nurses' understanding of antihypertensive medication adverse effects in Basra, highlighting a critical gap in knowledge and the need for targeted educational interventions. Implications: Enhancing academic and practical training for nurses is essential to improve patient care and adherence to hypertension treatments. Future research should focus on developing and implementing educational programs and continuous assessment frameworks to ensure nurses are well-equipped to manage and communicate the adverse effects of antihypertensive medications. By addressing these gaps, healthcare providers can better support patients in adhering to their treatment regimens, ultimately reducing cardiovascular risks and improving patient outcomes. Highlights: Knowledge Gap: Only 49.78% of nurses confident about antihypertensive medication adverse effects. Implications: Enhance nurse training to improve patient care and treatment adherence. Future Research: Develop educational interventions and continuous assessment frameworks for nurses. Keywords: Antihypertensive Medications, Nurse Knowledge, Adverse Effects, Hypertension, Patient Adherence